2018
DOI: 10.1111/bph.14362
|View full text |Cite
|
Sign up to set email alerts
|

Platelets, autotaxin and lysophosphatidic acid signalling: win‐win factors for cancer metastasis

Abstract: Platelets play a crucial role in the survival of metastatic cells in the blood circulation. The interaction of tumour cells with platelets leads to the production of plethoric factors among which our review will focus on lysophosphatidic acid (LPA), because platelets are the highest producers of this bioactive lysophospholipid in the organism. LPA promotes platelet aggregation, and blocking platelet function decreases LPA signalling and leads to inhibition of breast cancer cell metastasis. Autotaxin (ATX), a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 103 publications
0
33
0
Order By: Relevance
“…In human breast cancer, serum ATX has since been investigated a novel biomarker for nodal disease [83]. More recent studies demonstrate that ATX produced by platelets provides LPA for establishing a hospitable niche for metastatic cancer cell seeding, further enhanced by additional signaling mediated by ATX binding to cell surface integrins at the sites of metastases [84,85]. Results from cBioPortal (www.cbioportal.org) [86,87].…”
Section: Maladaptive Effects Of Excessive Atx Secretion and Lpa Signamentioning
confidence: 99%
“…In human breast cancer, serum ATX has since been investigated a novel biomarker for nodal disease [83]. More recent studies demonstrate that ATX produced by platelets provides LPA for establishing a hospitable niche for metastatic cancer cell seeding, further enhanced by additional signaling mediated by ATX binding to cell surface integrins at the sites of metastases [84,85]. Results from cBioPortal (www.cbioportal.org) [86,87].…”
Section: Maladaptive Effects Of Excessive Atx Secretion and Lpa Signamentioning
confidence: 99%
“…These experiments on ATX mRNA expression provide information on where ATX is produced before it is secreted into the tumor microenvironment where it attaches to adjacent cells including cancer cells by binding to integrins and syndecan-4. This binding appears to selectively channel LPA signaling to LPA receptors [ 68 , 69 , 70 , 71 ]. It is, therefore, concluded that most of the ATX that mediates LPA signaling is produced by adipocytes, fibroblasts, and tumor-associated stromal cells rather than the breast cancer cells themselves.…”
Section: Role Of Adipose Tissue As a Source Of Atx Production In Bmentioning
confidence: 99%
“…Secreted ATX binds to integrins and syndecan-4 on the surface of neighboring cells, including cancer cells. This binding appears to selectively channel LPA signaling to LPA receptors [ 68 , 69 , 70 , 71 ], which could be an important part of cancer progression.…”
Section: Influence Of Obesity On Breast Cancermentioning
confidence: 99%
“…ATX is detected in platelet α-granules. Functionally active ATX is eventually released following tumor cell-induced platelet aggregation, thereby promoting metastasis [ 66 ].…”
Section: Lplsmentioning
confidence: 99%